Effect of taro tuber silage (Colocasia esculenta [L.] Schott) on productive and reproductive indicators in F1 Landrace x Duroc sows - Caicedo, Willan Orlando (2020)
The effect of taro tuber silage (Colocasia esculenta [L.] Schott) on productive and reproductive indicators of commercial sows in pregnancy and lactation was evaluated. Forty F1 Landrace x Duroc sows were used, with an initial body weight of 174.2 ± 2.6 kg. The sows were randomly distributed in two diets. During pregnancy, 0 and 30% silage was included in the diet and the final weight of pregnant sows (FWPS), total number of piglets born at birth (TNPBB), total number of piglets born alive at delivery (TNPBAB), weight of litter at birth (WLB), weight of piglets at birth (WPB), feed consumption per sow in gestation (FCSG) and the cost of feeding in gestation (CFG). In lactation, 0 and 10% silage was included in the diet and the final weight of lactating sows (FWLS), number of piglets weaned per sow (NPWS), weight of piglets at weaning (WPW), weight of litter at weaning (WLW), days for the onset of post-weaning heat (DOPWH), days for conception from weaning (DCFW), feed intake per sow in lactation (FISL) and the cost of feeding in lactation (CFL). In pregnancy there were no significant differences for FWPS, TNPBB, TNPBAB, WLB, WPB and FCSG, but the CFG was lower in sows fed silage (p <0.05). In lactation there was no effect for FWLS, NPWS, WPW, WLW, DOPWH and DCFW, but the FISL and CFL were better (p <0.05) in the sows that consumed silage. It is concluded that the inclusion of silage of taro tubers in the diet of commercial sows in pregnancy and lactation did not affect the productive and reproductive indicators, but reduced feeding costs.